If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -3(-4 + m) = 7m + 32 6m + (-4 * -3 + m * -3) = 7m + 32 6m + (12 + -3m) = 7m + 32 Reorder the terms: 12 + 6m + -3m = 7m + 32 Combine like terms: 6m + -3m = 3m 12 + 3m = 7m + 32 Reorder the terms: 12 + 3m = 32 + 7m Solving 12 + 3m = 32 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. 12 + 3m + -7m = 32 + 7m + -7m Combine like terms: 3m + -7m = -4m 12 + -4m = 32 + 7m + -7m Combine like terms: 7m + -7m = 0 12 + -4m = 32 + 0 12 + -4m = 32 Add '-12' to each side of the equation. 12 + -12 + -4m = 32 + -12 Combine like terms: 12 + -12 = 0 0 + -4m = 32 + -12 -4m = 32 + -12 Combine like terms: 32 + -12 = 20 -4m = 20 Divide each side by '-4'. m = -5 Simplifying m = -5
| x(4x-3)+x(2x-3)=(6x+7)(x-2) | | -(2x+2)-1=-x-(x+3) | | -108=12b | | |x|=-3 | | 2(3-x)=-2(x-4) | | 5x-10=2x+35 | | 3y^5+81y^2= | | -125=5x-3(-4x+2) | | 5+3x+4x=19 | | -4y+12y=16 | | 2x-8+3x=5x-4 | | -2x^2+6x+4=y | | -3/2= | | 21X-3=15X+15 | | 3x(x-6)=11+(x-1)(3x-1) | | 3ax-4y=8 | | -1(-5-6x)=4(5x+3) | | 2k+8=-5(k-3) | | n+7=3N-1 | | -0.16p-0.05(5-5p)=0.05(p-3)-0.1 | | 7y+1-2y=26 | | (3x+4)+(4x-11)= | | -6(-2+3a)=-78 | | 20x+5=24-1 | | 2+a/4=3/5 | | 8y+3(y-7)=4(y+2)-4 | | -221=13n | | (4x+5)(9x-6)=0 | | 8n+n=54 | | 7x-71=19x+157 | | 16x^3-8=x-128x^2 | | 378-18X=16X |